Delineating the Interplay of Social Preferences and Explicit Incentives: An Agent-Based Simulation in a Public Goods Paradigm - Colasante, Annarita; Gil-Gallen, Sara; Morone, Andrea (Computational economics, 2025)
The present research aimed at investigating changes in contributions made within a public goods game (PGG) across varying conditions: a standard PGG, a PGG involving risky returns, and a PGG involving competition for heterogeneous returns. The empirical results, collected through a one-shot laboratory experiment, informed the classification of subject types and facilitated the calibration of an agent-based model (ABM). This model, populated by heterogeneous agents differentiated by social preferences, served two primary purposes: first, to analyze changes in contributions made under the specified conditions; and second, to evaluate the effect of varying proportions of unconditional cooperators. To achieve these aims, we compared contributions made under different incentive schemes and varying compositions of unconditional cooperators and free riders. The analysis enabled us to assess whether cooperation was better sustained by enhancing incentives or fostering prosocial preferences. Notably, the findings suggest that, while the most effective strategy for sustaining contributions is a monetary incentive involving competition for the highest return, a comparable outcome can be achieved by shaping individual preferences. The results point to the multifaceted nature of human cooperation and the potential for non-monetary incentives to shape cooperative behavior.